Inflation Dynamics in the Dominican Republic - Williams, Oral (IMF Working Papers; Working Paper ;, 2004)
This paper investigates the determinants of inflation in the Dominican Republic during 1991-2002, a period characterized by remarkable macroeconomic stability and growth. By developing a parsimonious and empirically stable error-correction model using quarterly observations, the paper finds that inflation is explained by changes in monetary aggregates, real output, foreign inflation, and the exchange rate.